Minimizing Permanent Pacemaker Following Repositionable Self-Expanding Transcatheter Aortic Valve Replacement - Jilaihawi, Hasan; Zhao, Zhengang; Du, Run; Staniloae, Cezar; Saric, Muhamed; Neuburger, Peter J.; Querijero, Michael; Vainrib, Alan; Hisamoto, Kazuhiro; Ibrahim, Homam; Collins, Tara; Clark, Emily; et al. (JACC. Cardiovascular interventions, 2019)
This study sought to minimize the risk of permanent pacemaker implantation (PPMI) with contemporary repositionable self-expanding transcatheter aortic valve replacement (TAVR). Self-expanding TAVR traditionally carries a high risk of PPMI. Limited data exist on the use of the repositionable devices to minimize this risk. At NYU Langone Health, 248 consecutive patients with severe aortic stenosis underwent TAVR under conscious sedation with repositionable self-expanding TAVR with a standard approach to device implantation. A detailed analysis of multiple factors contributing to PPMI was performed; this was used to generate an anatomically guided MInimizing Depth According to the membranous Septum (MIDAS) approach to device implantation, aiming for pre-release depth in relation to the noncoronary cusp of less than the length of the membranous septum (MS). Right bundle branch block, MS length, largest device size (Evolut 34 XL; Medtronic, Minneapolis, Minnesota), and implant depth > MS length predicted PPMI. On multivariate analysis, only implant depth > MS length (odds ratio: 8.04; 95% confidence interval: 2.58 to 25.04; p < 0.001) and Evolut 34 XL (odds ratio: 4.96; 95% confidence interval: 1.68 to 14.63; p = 0.004) were independent predictors of PPMI. The MIDAS approach was applied prospectively to a consecutive series of 100 patients, with operators aiming to position the device at a depth of < MS length whenever possible; this reduced the new PPMI rate from 9.7% (24 of 248) in the standard cohort to 3.0% (p = 0.035), and the rate of new left bundle branch block from 25.8% to 9% (p < 0.001). Using a patient-specific MIDAS approach to device implantation, repositionable self-expanding TAVR achieved very low and predictable rates of PPMI which are significantly lower than previously reported with self-expanding TAVR. [Display omitted]